Learning styles used by first-year undergraduate students in Medical Sciences. Cienfuegos, 2019-2020 - María Cristina Núñez Martínez; Lizgrace Llano Arana; Addys Teresita Stable Rodríguez; Ana Lidia Suárez Denis; Rosa María Masot Rivero; Daylis García Morales (Medisur)
Background: the learning style is directly related to the strategies that a student uses to learn something. One way to understand it would be to think of the learning style as the statistical mean of all the strategies used. Therefore, the major trends correspond to the most used strategies. Objective: to determine the strategies and learning styles used by first-year students of medical science degrees, during the teaching-educational process of the 2019-2020 academic year. Methods: descriptive and retrospective study about the relationship between strategies, learning styles and the quality of teaching. From the universe of 152 first-year students from the selected careers, a sample of 121 was determined, representing 80.6%. The observation of the process, the documentary analysis, the application of surveys and the Kolb learning test were used. The results were statistically processed, applying the Microsoft Excel spreadsheet and the SPSS professional package for Windows version 11.0. Results: the learning strategies and styles used by the students were identified, relating them to the academic results of the first year of the degree. The information recirculation strategy and the visual learning style predominated. When applying Kolb's wheel of learning, the theoretical or convergent type of student prevailed. Conclusions: the quality of the promotion achieved by the students can be considered satisfactory, because most of the evaluative results are located in the excellent and good categories.